The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/wnr.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic β2-receptor mediates itch hypersensitivity following heterotypic chronic stress in rats

Abstract: Chronic stress is widely considered to trigger or enhance itch, especially for pruritic dermatitis. However, the molecular mechanisms linking chronic stress and itch are still unknown. The present study aimed to elucidate the role of adrenergic signaling in itch hypersensitivity following heterotypic chronic intermittent stress (HIS) in rats. HIS significantly increased hindlimb scratching, but not forepaw swiping, induced by intradermal injection of 5-hydroxytryptamine (5-HT) in the rat cheek. Coadministratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…As described previously646566, we intradermally injected chemicals into the cheek of rats. Rats were shaved on cheeks (approx.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described previously646566, we intradermally injected chemicals into the cheek of rats. Rats were shaved on cheeks (approx.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described4366, tail immersion test was employed to determine heat pain sensitivity in rats. Briefly, the terminal 3 cm of a rat’s tail was immersed in hot water bath at 52 °C and the latency of tail flick was recorded with a cutoff time of 15 seconds to avoid tissue damage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Atenolol was reported to be effective in treating IAP. 83 Propranolol's therapeutic effect in treating IAP may also be explained by its role as an antagonist for certain serotonin receptors. 82 Recently, researchers discovered that injection of 5-hydroxytryptamine (5-HT) can induce scratching in na€ ıve rats.…”
Section: Idiopathic Aquagenic Pruritusmentioning
confidence: 99%
“…Peng et al. () found that chronic stress significantly enhances the scratching number when administrating 5‐HT into cheek skin in rats, and β 2 ‐adrenoceptors may mediate itch hypersensitivity via upregulating proinflammatory factors, such as TNF‐α in the skin. All the studies mentioned previously concentrated on the facilitative effects of chronic stress (depression) on itch hypersensitivity instead of the effects of chronic itch on depression.…”
Section: Introductionmentioning
confidence: 99%